Controlling Emotions from the Al-Qur'an Perspective - Siti Nurfitriani Wardah; Muhtar Gojali (Gunung Djati Conference Series, 2021)
This study aims to discuss how to control emotions from the perspective of the Qur'an. The method used is a qualitative method through literature study with a content analysis approach. The results and discussion of this study include general views of emotions, texts and interpretations of verses of the Qur'an about emotional control, and how to control emotions from the perspective of the Qur'an. The conclusion of the study is that there are many verses of the Qur'an that talk about emotional control that can be applied by humans in general so that emotions are well directed and do not cause chaos and damage. This study recommends doing research with quantitative methods based on facts in the field so that it can be a real solution for human life in general.